Violence,fantasy,memory and testimony in MDA's ways of dying and she plays with the darkness - Foster, Sue-Ann Anita (My University, 2007)
This research report analyzes the representation of violence in Zakes Mda’s Ways of Dying and She Plays with the Darkness. Ways of Dying questions whether social stability and democracy would be fully realized in post-apartheid South Africa as is predicted in Black South African literature written between 1970 and 1994. Mda’s disillusionment is shown in his examination of undemocratic and violent practices committed within the liberation movement against the oppressed and of “black-on-black” violence in South Africa. She Plays with Darkness posits that political corruption and repression in Lesotho occurred as a result of the erosion of African values and traditions, which caused political leaders and the middleclass to dismiss the well-being of their society for personal gains. For Mda, however, societies and individuals can be redeemed from violence through memory, testimony, fantasy and art. Both novels reveal his endeavor to creatively narrate the experience of violence.
Student Number : 0401052V - MA research report - School of Literature and Language Studies - Faculty of Humanities
Keywords: social stability; democracy; post-apartheid South Africa; Black South African literature; "She Plays with Darkness"; Mda; violence